Barriers and facilitators to the integration of cervical cancer screening and treatment service with antiretroviral therapy follow-up clinics for women living with HIV in Northwest Ethiopia: a qualitative study - Ferede, Kelemework Gashinet; Ferede, Addisu Gasheneit; Abdu, Asiya Mohammed; Yazew, Birhaneslasie Gebeyehu; Aynalem, Zewdu Bishaw; Fenta, Eneyew Talie; Mekonnen, Daniel Shitu; Bantie, Berihun; Tsegaye, Gebiyaw Wudie (Frontiers in Public Health, 2025)
BackgroundWomen living with HIV (WLHIV) face a significantly elevated risk of invasive cervical cancer, an AIDS-defining malignancy. Integrated cervical cancer screening (CCS) and HIV care are essential for optimal management; however, these services remain largely unintegrated in Ethiopia, resulting in low screening coverage. This study aimed to explore the barriers and facilitators to integrating CCS and preventive treatment services within antiretroviral therapy (ART) follow-up clinics for WLHIV in Northwest Ethiopia.MethodsA phenomenological study was conducted from January to April 2023 among 33 participants across nine purposively selected health facilities in Northwest Ethiopia. Data were collected using focus group discussions and in-depth key informant interviews. Audio-recorded data were transcribed, translated, and coded, followed by thematic analysis using Atlas. Ti 7 software.ResultsKey barriers to integration included inadequate facilities, a shortage of dually trained clinicians, low healthcare provider motivation, the absence of integration policies, and a lack of evidence on integration effectiveness. Facilitators included the accessibility of free ART and CCS services, the simplicity of the visual inspection with acetic acid (VIA) screening method, the availability of staff trained in either ART or CCS, and patient familiarity with ART providers.ConclusionIntegrating cervical cancer screening with HIV care in Northwest Ethiopia encounters substantial obstacles, including facility limitations, clinician training deficits, motivational issues, policy gaps, and a lack of evidence. However, accessible services, the VIA method’s simplicity, and existing staff training provide opportunities for successful integration. Addressing these barriers and leveraging facilitators is crucial to improve integrated service delivery and reduce related mortality among WLHIV.